The Study of Ammatoa Customary Forest Management by the Kajang Tribe for the Development of a Conservation-Based Learning (CBL) Model Integrated with Local Wisdom - Akhmad Kurnia; Muhammad Yasir Arafat; Muhammad Wajdi; Usman Usman; Fadhil Surur (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
This study aims to examine the effectiveness of applying the Conservation Based Learning (CBL) model integrated with local wisdom in improving the environmental literacy of fifth-grade students at SDN 351 Kawasan Ammatoa, Bulukumba Regency, South Sulawesi. Using a quasi-experimental design with a non-equivalent control group, this study involved two classes, namely an experimental class taught using the CBL model and a control class taught using conventional methods. Data collection was conducted through learning outcome tests in the form of multiple-choice and essay questions that measured students' environmental literacy, which included understanding conservation concepts, the ability to analyze environmental problems, and the application of knowledge in daily life. The results showed that the application of the CBL model integrated with local wisdom had a significant impact on improving students' environmental literacy, with the average posttest score for the experimental group reaching 86.00, while the control group only scored 61.81. Hypothesis testing using an independent t-test showed a significant difference between the two groups (p < 0.05). In addition, N-Gain score analysis revealed a higher increase in the experimental group (0.76) compared to the control group (0.35), indicating that the CBL model is more effective in improving environmental literacy. Thus, this study confirms that the CBL model, which integrates local wisdom, can significantly improve students' understanding, analysis, and application of environmental knowledge, which is important for shaping sustainable environmental awareness